The Efforts of Yogyakarta Regional Disaster Management Agency (BPBD) in Empowering Flood Disaster Mitigation on Banks of the Gajah Wong River - Tristanti; Akhmad Rofiq; Erma Kusumawardani (Postgraduate, University of Mataram, 2024)
The purpose of this study is to determine the efforts of BPBD in flood disaster management on the banks of the Gajah Wong River. The method used in this research is a qualitative descriptive method that emphasises the process rather than the results achieved. Data collection techniques were carried out by means of observation, interviews and documentation. The targets in this research are BPBD and people who live on the banks of the Gajah Wong River which are often affected by flooding. The data analysis technique uses the Miles and Huberman approach which consists of several stages, namely data collection, data reduction, data presentation to verification. In this study, researchers used data validity techniques using a data triangulation approach. The results of the research conducted are that in handling flood disasters, BPBD has taken preventive measures through the KTB (Disaster Response Village) training programme, it is hoped that the programm will be able to solve flood problems because the community becomes responsive to disasters such as floods that often occur when rainfall is high. The flood disaster that occurred in Gajah Wong River did not cause a big impact.